Review on Organic Waste Materials in Value of Nitrogen, Phosphorus and Potassium - Abdul Malek, Khairul Zaman; Abdul Razak, Nur Alia; Rosman, Mohamad Syahmie; Saliman, Muhammad Haiqal (Multidisciplinary Applied Research and Innovation, 2021)
Fertilizers divided into organic fertilizers and chemical fertilizers. Chemical fertilizers contain chemicals which can harmful to plants if used regularly. This problem will lead to other problems such as plants are no longer fertile and harmful to the environment. Some of the harm chemical fertilizers may cause waterway pollution, chemical burn to crops, increased air pollution, acidification of soil and mineral depletion of soil. An initiative has been designed to reduce the usage of chemical fertilizers by using organic waste materials such as eggshells, banana peels, spent coffee grounds, onion peels and spent grain. From 179 journals have been published between 2000 until 2020, only 30 journals has been selected. The primary objective of this study is to review the effectiveness of the organic waste materials in aspect of N, P, K value. 17 journals complied N, P, K suggested range with different ingredients. Organic waste materials able to supply enough needed nutrients to plants which can be considered as organic fertilizer.